2015
DOI: 10.1039/c5ra18462b
|View full text |Cite
|
Sign up to set email alerts
|

Modernization of surfactant chemistry in the age of gemini and bio-surfactants: a review

Abstract: This review contains elaborate discussions on the efficiencies of gemini and bio-surfactants as modern generation green chemicals in various fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 47 publications
2
59
0
Order By: Relevance
“…There is another class of novel surfactant identified by Menger and Littau in 1991, containing more than one hydrophilic group linked by a spacer (Figure ) . This spacer groups enhances the hydrophobic nature of the Gemini surfactants compared to the monomeric surfactants . The hydrophilic heads may be cationic, anionic and neutral or zwitter ionic in nature and the hydrophobic tail may be long or short in size.…”
Section: Classificationmentioning
confidence: 99%
“…There is another class of novel surfactant identified by Menger and Littau in 1991, containing more than one hydrophilic group linked by a spacer (Figure ) . This spacer groups enhances the hydrophobic nature of the Gemini surfactants compared to the monomeric surfactants . The hydrophilic heads may be cationic, anionic and neutral or zwitter ionic in nature and the hydrophobic tail may be long or short in size.…”
Section: Classificationmentioning
confidence: 99%
“…The used micellar catalysts can some times be easily recycled in the reaction. Micelles and other types of surfactant aggregates are effective catalysts for a wide range of organic reactions [22][23][24]. It has been already reported that reaction rates are affected by solubilization of reactants, changes in local concentrations due to compartmentalization of reaction media, and changes in medium properties [25].…”
Section: Introductionmentioning
confidence: 99%
“…Biosurfactants have several advantages over chemically synthesized surfactants, which are lower toxicity, having specific functional groups with targeted actions, and more effective at extreme temperatures or pH values (Jiménez‐Peñalver et al, ). The commercial potential of biosurfactants is based on these advantages (Mao et al, ; Mondal et al, ; Vijayakumar and Saravanan, ). Being produced from renewable resources, biosurfactants facilitate sustainable development.…”
Section: Introductionmentioning
confidence: 99%